Poor or Just Feeling Poor-Situation in Albania - Bici, Ruzhdie; Mancellari, Ahmet (European Scientific Journal, ESJ, 2017)
There exist different methods and definition how to measure poverty. It can be measured by income or consumption, objectively or as a perception of individuals for their socio-economic situation.The objective and subjective poverty are highly correlated and both are influenced by socioeconomic factors. Till now, it is the objective poverty mostly considered while the subjective one has been analyzed only as a part of it. Assessments of the subjective poverty are more scarce, especially in the case of transition countries. Different studies proposed advantages and disadvantages of using each method. The significance of different factors shows the characteristics and the trend of monetary or subjective poverty. The national poverty is Albania is calculated through monetary poverty. There are a set of influenced factors related with household composition, geographic division, education and other socio-economic indicators. In this paper we analyze the perception of individuals for the poverty, the relationship of this perception with the objective poverty, and the socio-demographic factors that influence the probability of being poor. There are used the data from the Albanian Living Standard Measurement Survey (LSMS).